Primary Sjögren's Syndrome - M. Šembera; R. Slezák; V. Radochová (Czech Dental Chamber, 2018)
Background: Primary Sjögren's syndrome is a progressive autoimmune disease that affects predominantly middle-aged women, typically in the fourth to sixth decenium. It is believed the third most common autoimmune disease after rheumatoid arthritis and systemic lupus erythematosus. The cause of the disease is not fully recognized but a combination of inherited disposition, influence of sex hormones, infectious and environmental factors has been assumed. The examination algorithm requires ophthalmological, dental and immuno-rheumatological examinations as per current diagnostic criteria are from 2016. Despite of all advances in diagnostic methods, the diagnosis of the primary Sjögren's syndrome remains rather difficult because of the variability of clinical manifestations. The disease manifests most often by xerostomia and xerophthalmia caused by a lymphocytic infiltration of the salivary and lacrimal glands. In addition, patients often suffer from various musculoskeletal, cutaneous, internal and gynecologic disorders, as well. Clinical manifestations of Sjögren's syndrome in the oral cavity are usually the initial symptoms. Oral signs may lead to the suspicion for the disease. Conclusion: The review deals with history, epidemiology, etiology and pathogenesis, immunopathology, diagnostics, clinical symptoms and therapy of the primary Sjögren's syndrome.